Universal Design for Learning in Adapted National-level Digital Mathematics Textbooks for Elementary School Students with Disabilities. Issue 1 (1st January 2023) - Lee, Okin; Shin, Mikyung
ABSTRACT: Learning mathematics in an inclusive classroom is challenging for many students with disabilities. The adapted digital mathematics textbooks for Grades 3 to 6 in South Korea were designed to support these students' access to the general mathematics curriculum. This study evaluates these textbooks according to the Universal Design for Learning (UDL) guidelines. The design features of the mathematics textbooks varied within and across various UDL checkpoints. Overall, the aspect of providing multiple means of action and expression was the most frequently observed, followed by providing multiple means of representation and providing multiple means of engagement. Special education teachers and textbook developers can use these results as a resource for designing curricula and lessons for students with disabilities in the inclusive classroom.